The prevalences of some rheumatic diseases in western Turkey: Havsa study - (:unkn) unknown (SPRINGER HEIDELBERG, 2012)
To study the prevalence major rheumatic diseases in western Turkey. This survey was conducted in Havsa which have a total population of 18,771. Physicians and interns visited every household, interviewed face to face a questionnaire about the symptoms of rheumatic disorders. The individuals replied positively to any question were examined at the nearest health center. Those have no objective findings related to any rheumatic diseases were excluded. People could not be clinically diagnosed were asked to come to the hospital for further evaluation. A total 17,835 of 18,771 residents participated. We estimated the prevalence of Beh double dagger et's Disease (BD) as 0.019%; ankylosing spondylitis: 0.120%; rheumatoid arthritis: 0.321%; knee osteoarthritis (OA): 5.351%; hand OA: 1.110%; hand and knee OA: 1.958%; total OA: 8.420%; primary Raynaud's: 1.192%; psoriasis: 0.424 %; psoriatic arthritis: 0.050%; rheumatic fever: 0.318%; rheumatic heart disease: 0.200%; inflammatory bowel disease: 0.023%; lupus: 0.059%; gout: 0.018%; systemic sclerosis: 0.022%; juvenile rheumatoid arthritis: 0.032%; temporal arteritis: 0.020%, and familial Mediterranean fever (FMF) as 0.006%. Figures were adjusted for age-sex of the general Turkish population. The prevalence's of BD and FMF are considerably lower in Havsa as compared to other regions in Turkey.
Keywords: Behcet's disease; Familial Mediterranean fever; Rheumatoid arthritis; Ankylosing spondylitis; Epidemiology; Psoriasis; SYSTEMIC-LUPUS-ERYTHEMATOSUS; INFLAMMATORY-BOWEL-DISEASE; JUVENILE IDIOPATHIC ARTHRITIS; FAMILIAL MEDITERRANEAN FEVER; RAYNAUDS-PHENOMENON; BEHCETS-DISEASE; ANKYLOSING-SPONDYLITIS; PSORIATIC-ARTHRITIS; GENERAL-POPULATION; URBAN-POPULATION